Restoration of the term in the administrative proceedings - Muzyczka, Karolina (Acta Universitatis Lodziensis. Folia Iuridica, 2015)
There are two basic types of terms in administrative proceedings. The first kind of terms concerns those which result directly from an act (these are in turn divided into final and instructional deadlines), the second type concerns extra periods and deadlines set by the administrative authority conducting the case. The main difference between the final and instructional terms boils down to the legal consequences that occur after non-compliance with them. In case of exceeding the limitation period by a party it comes to the ineffectiveness of the activities undertaken, while exceeding the limitation period by a body, in turn, causes a loss of its jurisdiction to rule in a matter. If you exceed the instructional term there are no such important legal consequences. Instructional deadlines can be either lengthened or shortened. This means that the party does not lose their right definitely to present specific requests. It is worth noting, however, that if you exceed the final deadline it is still possible to restore it. Restoration of term is always at the request of parties. Under binding provisions a party has seven days to present an application. This time limit begins from the moment (as of) cessation of a reason for failure.